Nuclear Receptors Regulate Intestinal Inflammation in the Context of IBD - Klepsch, Victoria; Moschen, Alexander R.; Tilg, Herbert; Baier, Gottfried; Hermann-Kleiter, Natascha (Frontiers in Immunology, 2019)
Gastrointestinal (GI) homeostasis is strongly dependent on nuclear receptor (NR) functions. They play a variety of roles ranging from nutrient uptake, sensing of microbial metabolites, regulation of epithelial intestinal cell integrity to shaping of the intestinal immune cell repertoire. Several NRs are associated with GI pathologies; therefore, systematic analysis of NR biology, the underlying molecular mechanisms, and regulation of target genes can be expected to help greatly in uncovering the course of GI diseases. Recently, an increasing number of NRs has been validated as potential drug targets for therapeutic intervention in patients with inflammatory bowel disease (IBD). Besides the classical glucocorticoids, especially PPARγ, VDR, or PXR-selective ligands are currently being tested with promising results in clinical IBD trials. Also, several pre-clinical animal studies are being performed with NRs. This review focuses on the complex biology of NRs and their context-dependent anti- or pro-inflammatory activities in the regulation of gastrointestinal barrier with special attention to NRs already pharmacologically targeted in clinic and pre-clinical IBD treatment regimens.